Third Party Logistics: Is asset intensity competition as asset for growth? - Kwa, Francis CH (2010)
Logistics trade journals, research literatures and annual reports from third party logistics firms claimed “Asset Intensity” strategy (asset-based, asset-light, non asset-based) is a strategy for superior financial performance. This thesis seeks to determine the origin and definition of the “Asset Intensity” strategy and its claim as a strategy for superior financial performance.